Nonreplicated DNA and DNA Fragments in T4 r(−) Bacteriophage Particles: Phenotypic Mixing of a Phage Protein - Carlson, K. (1974)
“Conservative phage” containing a genome derived from an infecting phage particle which has not undergone replication in the cell but nevertheless has become encapsulated and released in a normal phage particle, are found after infection of Escherichia coli with rII(−) or rI(−) mutants under conditions which result in rapid lysis. If such conservative phage are derived from a mixed infection with v(+) and v(1) phage, they display phenotypic mixing of the v gene product (an endonuclease carried in the phage particle). Populations of rI and rII mutant phage grown under conditions of rapid lysis include particles containing short DNA fragments. It is suggested that a “maturation defect”, common to rI and rII mutants, but absent in rIII mutants, may account for the encapsulation of nonreplicated DNA as well as that of the DNA fragments.